C OMBINING DISTRIBUTED G ENERATIONAND E NERGY M ANAGEMENT TECHNOLOGIES TO ACHIEVE E NERGY C OST SAVINGS - Eberly, David A. (Distributed Generation & Alternative Energy Journal, 2004)
Applying energy management systems to building control systems provides the capability to merge several conventional and non-conven- tional cost reduction strategies. Energy consumption reductions are derived from conventional strategies such as temperature resets in air and water handling systems, chiller plant optimization, HVAC scheduling optimization, and automa- tion of lighting system operation. These activities alone represent a sig- nificant potential for energy savings at a facility. In the current era of deregulation, both the natural gas and electric utility suppliers find themselves in a changing and more competitive business environment. As a result, creative rate options have been devel- oped to retain current customers and to attract new ones. Electric utility rates, including RTP (real time pricing), and inter- ruptible service (IS) have been available to PJM (Pennsylvania, New Jer- sey, and Maryland) customers since 1994. On-site power generation sys- tems have been utilized by many facilities to take advantage of these rates to reduce electric costs. Energy management systems are also used to manage the operation of on-site power generation systems, conven- tionally for power outages or to improve power quality. This article describes the installation of a 2,000 kW on-site power generation system, and the integration of its capabilities with a facility energy management system to exploit an interruptible electric service rate. These systems are installed at a 600-acre corporate campus site, located in central Pennsylvania. There are 28 buildings occupying the site, enclosing approximately 1,000,000 square feet of conditioned space By combining capabilities of the EMS (energy management system) and on-site power generation systems, the subject facility can interrupt more than 70 % of its on-peak summer electric load, within 2 hours after a curtail- ment request, utilizing minimal staff, and causing minimal noticeable change to employees working at the site. The application of these sys- tems has reduced the Campus annual electricity costs by more than 25% since implementation in July 2001.